CSF Fistulas after Transsphenoidal Pituitary Surgery—A Solved Problem? - Malik, Muhammad Usman; Aberle, Jens C.; Flitsch, Joerg (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Objective Transsphenoidal surgery has been the gold standard for intra- and suprasellar lesions as well as some extrasellar pathologies for more than 40 years. This approach, with proper surgical expertise, is very safe with a low morbidity and mortality rate. However, as with every surgical treatment, complications can occur and may result in serious consequences for the patient. The goal of this article is to focus on cerebrospinal fluid (CSF) fistulas after transsphenoidal surgery and discuss possible risk factors and treatment options, including less common procedures in persistent CSF fistulas.Methods Over a period of 24 months, 339 consecutive patients underwent a total of 363 transsphenoidal surgeries for different pathologies in our institution. There were 282 patients with pituitary adenomas and 57 patients with nonadenomateous lesions.Results CSF fistulas occurred in total of six patients (1.77%), most frequently after surgery for nonadenomateous lesions (7%). The rate was only 0.7% after surgery for pituitary adenomas. In three patients, a simple resurgery with repacking of the sella using muscle, fat, and fibrin glue was performed. All three patients received a lumbar drainage for 5 days as well. All three patients had recurrent CSF fistulas despite surgical repair, requiring multiple resurgeries. In two patients, the implantation of a ventriculoperitoneal (vp) shunt with programmable valve for continuous lowering of the CSF pressure was required. In both patients, the vp shunt was explanted 2 to 3 months after the last proven rhinorrhea. Out of the 339, 2 patients developed meningitis due to CSF fistulas (0.59%).Conclusions CSF fistulas continue to present a problem after transsphenoidal surgery and require sophisticated technical measures to treat this complication. Failure after repair can occur and necessitates more intense treatment modalities. The usage of the transsphenoidal approach in other skull base lesions leads to higher rates of CSF fistulas and subsequently higher frequency of meningitis.
Keywords: transsphenoidal; cerebrospinal fluid fistulas; pituitary surgery; cerebrospinal fluid leak